A Multi-Stakeholder Process to Transform a Community-based Screening and Referral Program to Implement Evidence-Based Depression Care. Issue 4 (3rd July 2016) - Pepin, Renee; Hoyt, Jessica; Seifert, Bernadette; Bartels, Stephen J.
Abstract : Background: Screening and referral for geriatric depression by service agencies is associated with poor treatment engagement indicating the need to transform services to directly provide depression care. Objective: To describe a multi-organization workgroup implementation planning process used to transform a community-based screening and referral program to provide a brief evidence-based intervention for older adults with depressive symptoms. Methods: An iterative implementation procedure used by a multi-stakeholder group that selected an evidence-based practice, planned implementation rollout, planned counselor training, and designed an implementation evaluation. Results: The workgroup successfully followed the implementation procedure and developed a plan for the implementation of an evidence-based intervention. Overall, the workgroup prioritized decisions that favored feasibility and low implementation burden. Conclusion: A multi-organization workgroup can benefit from a semi-structured implementation planning procedure because it provides all stakeholders with a shared roadmap for implementation planning.